Patih Bersidig Cartu Tingkatkan Kompetensi Guru Mata Pelajaran IPA di Era Revolusi Industri 4.0 - Lilik Rahmawati (Universitas Semarang, 2023)
The condition of most science teachers in the Grobogan District has not been optimal in utilizing digital technology in the learning process. Training is a form of activity chosen by the school superintendent to guide science teachers in Grobogan in collaboration with subject-teacher deliberations (MGMP). The purpose of this best practice is to describe the implementation, results, and impact of digital-based training are a surefire way